2004
DOI: 10.1056/nejmoa033402
|View full text |Cite|
|
Sign up to set email alerts
|

Anti–Interleukin-12 Antibody for Active Crohn's Disease

Abstract: Treatment with a monoclonal antibody against interleukin-12 may induce clinical responses and remissions in patients with active Crohn's disease. This treatment is associated with decreases in Th1-mediated inflammatory cytokines at the site of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
467
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 800 publications
(503 citation statements)
references
References 20 publications
20
467
1
10
Order By: Relevance
“…Furthermore, monoclonal antibodies targeting the p40 subunit of IL-12 and IL-23 were effective in treating patients with CD in preliminary studies. 42 We conclude that MST1 is the most likely IBD/PSC-associated gene defined by the rs3197999 association and rs3197999 itself is the genetic variant causing disease association. The gain of function caused by rs3197999 has at least two effects, which would be expected to promote local inflammation: (1) increased attraction of macrophages to chemotactic agents and (2) increased macrophage proliferation.…”
Section: Analysis Of Msp Clonesmentioning
confidence: 74%
“…Furthermore, monoclonal antibodies targeting the p40 subunit of IL-12 and IL-23 were effective in treating patients with CD in preliminary studies. 42 We conclude that MST1 is the most likely IBD/PSC-associated gene defined by the rs3197999 association and rs3197999 itself is the genetic variant causing disease association. The gain of function caused by rs3197999 has at least two effects, which would be expected to promote local inflammation: (1) increased attraction of macrophages to chemotactic agents and (2) increased macrophage proliferation.…”
Section: Analysis Of Msp Clonesmentioning
confidence: 74%
“…Subsequently, various antibodies against IL 12-IL 23 p40 and IL 23 p19 subunits were developed for clinical trials (such as ABT 874, ustekinumab, risanki zumab, LY 2525623, AMG139/MEDI2079 and guselku mab) [105][106][107] . Studies with ABT 874 and ustekinumab as p40 blockers demonstrated higher response rates in patients with Crohn's disease than placebo.…”
Section: T Cellmentioning
confidence: 99%
“…Understanding the complex, pleiotropic action of IL-23R and the specific variants that give rise to each of these autoimmune traits will undoubtedly increase progress in our understanding of the molecular pathophysiology underlying these chronic autoinflammatory conditions. Moreover, coupled with the recent advances in autoinflammatory biology, the IL23R variants described herein may lead to a deeper understanding of molecular action of targeted therapeutics such as the efficacious IL-12/IL-23 monoclonal antibodies [44][45][46] and prove useful in autoinflammatory pharmacogenetics.…”
Section: Discussionmentioning
confidence: 98%
“…37,38 (2) (5) clinical studies have shown dramatic efficacy of IL-12p40 antibodies in reducing symptoms in a high percentage of psoriatic subjects 44,45 and those with active Crohn's disease. 46 These diverse studies have conspired to highlight the central function of the IL-23/T H -17 axis in mediating chronic inflammatory disease pathogenesis, downplaying the role of IL-12. Hence, full genetic description of both IL12B and IL23R, genes encoding for critical proteins in the IL-23/T H -17 response, is necessary to delineate specific variants predisposing and protective of disease and to further our understanding of the molecular pathobiology of autoinflammatory phenotypes.…”
Section: Discussionmentioning
confidence: 99%